2022
DOI: 10.3389/fcimb.2022.1022879
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Pediococcus pentosaceus ameliorates MPTP-induced oxidative stress via regulating the gut microbiota–gut–brain axis

Abstract: Recent evidence demonstrated that functional bacteria were involved in the regulation of Parkinson’s disease (PD). However, the mechanism of probiotics in improving PD was unclear. Here the antioxidant effect and the mechanism of probiotics Pediococcus pentosaceus (PP) on PD were studied by regulating the gut–brain axis. In this study, male C57BL/6J mice were injected with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) intraperitoneally to establish a PD model and were then treated with PP for 4 weeks. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…This can have a complimentary effect in that the butyrate levels are restored in addition to suppressing the outgrowth of other non-beneficial and sometimes inflammatory bacteria. After the administration of probiotics, prebiotic fibers (including oligosaccharides), or a high-fiber diet several studies investigated the gut microbial changes and the consequent effects on PD symptoms ( Perez-Pardo et al, 2017 ; 2018 ; Srivastav et al, 2019 ; Ghyselinck et al, 2021 ; Li T. et al, 2022 ; Pan et al, 2022 ) (Studies are summarized in Table 2 ).…”
Section: Therapeutic Approaches Exploiting Butyrate In Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…This can have a complimentary effect in that the butyrate levels are restored in addition to suppressing the outgrowth of other non-beneficial and sometimes inflammatory bacteria. After the administration of probiotics, prebiotic fibers (including oligosaccharides), or a high-fiber diet several studies investigated the gut microbial changes and the consequent effects on PD symptoms ( Perez-Pardo et al, 2017 ; 2018 ; Srivastav et al, 2019 ; Ghyselinck et al, 2021 ; Li T. et al, 2022 ; Pan et al, 2022 ) (Studies are summarized in Table 2 ).…”
Section: Therapeutic Approaches Exploiting Butyrate In Pdmentioning
confidence: 99%
“…In animal models of PD, the supplementation of various probiotics, all belonging to the phylum Bacillota, resulted in gut microbiota composition alterations and is associated with increased levels of fecal butyrate ( Srivastav et al, 2019 ; Li T. et al, 2022 ; Pan et al, 2022 ). When investigating the neuroprotective effects of this supplementation in the brain, it was found that DA neurons were protected from cell death, glial cell hyperactivation was suppressed, and neuroinflammation was reduced ( Srivastav et al, 2019 ; Li T. et al, 2022 ).…”
Section: Therapeutic Approaches Exploiting Butyrate In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to live bacteria, postbiotics have more versatile characteristics, including a clear chemical structure, safe dosage parameters, and a lack of the potential risks associated with live bacteria. As a result, postbiotics have emerged as a promising strategy for promoting healthy food and treating diseases [ 13 , 14 , 15 ]. The cell-free supernatant (CFS) produced by bacterial fermentation contains postbiotics secreted by the indicated probiotics, which have been shown to have protective effects on the intestine similar to those of live bacteria, suggesting that their active substances come from soluble molecules in the supernatant that can regulate the secretion of inflammatory factors or activate related immune cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, further evidence showed the level of GABA was reduced in neuropsychiatric diseases [ 29 , 30 ]. Interestingly, intestinal microbiota, such as Lactobacillus SPP and Bifidobacterium , can produce GABA mediators [ 31 ]. It was also evidenced that treatment with probiotics for 4 weeks significantly improved the gastrointestinal symptoms in patients with Parkinson’s disease through the secretion of GABA factors.…”
Section: Introductionmentioning
confidence: 99%